Analysis of MgFeCu-Layered Double Hydroxides with Different Interlamellar Anions for Efficient Removal of Dye in Wastewater Treatment - Muhammad Syaza bin Mohd Sahabudin; Norrizal Mustaffa; Nurasyikin Misdan (Journal of Advanced Mechanical Engineering Applications, 2025)
Synthetic dyes, widely used in industries like textiles, leather, and paper, pose a significant global concern for water pollution due to their resistance to conventional wastewater treatment, causing toxic, carcinogenic, and mutagenic effects, endangering aquatic life and disrupting natural processes like photosynthesis. The study analyzes the adsorption of as-prepared MgFeCu-LDH with varied interlamellar anions (CO?²?, SO?²?, NO??) on dye wastewater, utilizing advanced techniques like Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) to identify LDH morphology and crystal structure, elucidating dye removal mechanisms. The methods and materials used in this study include synthesizing MgFeCu-Layered Double Hydroxides with various interlamellar anions using co-precipitation and involved weighing 50 mg of LDH and 30 ml of dye solution, equilibrating samples, and analyzing UV analysis and storage to determine the amount of adsorbed MO in the supernatants, followed by adsorption kinetic studies to evaluate the efficiency and mechanisms of dye removal from wastewater, focusing on pseudo-second-order kinetic models to determine the dominant adsorption processes. MgFeCu-SO? LDH removes dyes from wastewater in 150 minutes using a second-order process, providing a quick, cost-effective, and environmentally friendly solution. The findings provide important insights into the development of novel materials to address the persistent problem of synthetic dye contamination in aquatic systems, highlight the potential of LDH materials for wastewater treatment, as they offer a scalable approach to dye removal via tailored chemical and structural properties.